Can Regulatory Oversight Help Firm Performance? Evidence from U.S. Commercial Banks - Stan Veuger; Kristin Wilson (American Enterprise Institute (AEI), 2015)
Information frictions between firms and regulators are typically seen as a means by which firms evade enforcement or, alternatively, a means through which they can limit rent-seeking behavior. In contrast, we argue that information frictions between firms and regulators reduce the efficiency of firms' compliance efforts, particularly when industry rules are open-ended or qualitative. We use physical distance between firms and regulators to test these competing theories of information exchange on a panel of U.S. community banks between 2001 and 2010. We exploit overlapping regulatory jurisdictions to generate plausibly exogenous variation in distance between bank and supervisor. We find that banks located at a greater distance from regulatory field offices face significantly higher administrative costs, at an average rate of about 20% of administrative costs per hour of travel time. These cost differences are not accompanied by differences in compliance outcomes, are not driven by endogenous regulator choice, and are stable over our time period. Further, the inefficiency of distant firms is negatively related to the scale of the jurisdiction in which they operate, suggesting that information spillovers within jurisdictions limit the uncertainty about regulatory expectations in decentralized oversight regimes.
Keywords: A; 330; Regulation